Géographie conflictuelle d’une ville : Rue Saint- Urbain de Mordecai Richler et Côte-des-Nègres de Mauricio Segura - Żurawska, Anna (Polskie Towarzystwo Badań Kanadyjskich, 2013)
The aim of the article is to examine Rue Saint-Urbain (The Street) by Mordecai Richler and Côte-des-Nègres by Mauricio Segura. Despite numerous differences between the two writers (their origins, languages of their literary expression, time of their artistic activity, etc.), their works share certain characteristics. The narrators of both novels are similar to each other in their sensitivity to the multicultural situation of their quarters, which may be regarded as a source of conflicts and absurdities. The comparative analysis of the two novels, focusing particularly on the literary visions of Montreal presented in both texts, explores the relationships not only between Quebeckers and immigrants, but also between various ethnic groups within the Quebecois metropolis.